Comparison of clinical and laboratory parameters in patients with migraine or tension-type headaches: A case-control study - Yılmaz, Murat; Teker, Handan; Bakkal, Tahsin; Canbasoglu Yılmaz, Aysen Tugba; Aydın Türkoğlu, Sule; Kuyucu, Serpil (Journal of Surgery and Medicine, 2021)
Background/Aim: Migraine and tension-type headaches (TTH) are common headache disorders that are not caused by or attributed to another disorder, and it is important to elucidate the clinical and laboratory features in patients with these diseases. This study aimed to compare the clinical and laboratory features of migraine patients with TTH. Methods: Nineteen patients with TTH, 73 patients with migraine, and 30 volunteers without headache who visited Bolu Abant Izzet Baysal Training and Research Hospital between January 2018 and December 2018 were included in this case-control study. Patients’ Fazekas score, age, gender, muscle score, hemogram parameters, parathyroid hormone, protein C, Protein S, Antithrombin III, low-density lipoprotein cholesterol, vitamin D, folate, vitamin B12 levels, antiphospholipid, anticardiolipin, thyroid autoantibodies, and ANA positivity were noted. Results: The mean age in the migraine, TTH, and control groups were 43.54 (11.60), 47.05 (12.09), and 47.23 (12.33) years, respectively (P=0.261). There was no difference between the groups in terms of gender distribution (P=0.115). The Fazekas scores of the migraine (1[0-3]) and TTH groups (1[0-3]) were higher than controls (0[0-2]) (P<0.001). Conclusion: Considering the Fazekas scores and antithrombin III levels in clinical and laboratory evaluation will be useful in the diagnosis and differentiation of migraine and TTH.